The Comparison of SARS-CoV-2, SARS-CoV, and MERS-CoV Genome and Spike Protein Variations - Choirun Nita Fikriani; I Kade Karisma Gita Ardana; Dwi Listyorini (Jurnal Riset Biologi dan Aplikasinya, 2021)
SARS-CoV-2 is a virus that has caused COVID-19 pandemic. This virus is a new variant of the SARS-CoV virus and also closely related to MERS-CoV, which caused similar acute respiratory infections. All these viruses recognize target cells by binding to the Receptor Binding Domain (RBD) on Spike protein with receptors. This study aimed to determine the SARS-CoV-2, MERS-CoV, and SARS-CoV genome structure, Spike protein sequence differences, and variations of RBDs Receptor Binding Motif (RBM). This research was using data mining approach. Genome sequences were downloaded from NCBI, except for Indonesian samples were downloaded from GISAID. Genomic structures, Spike sequence, and RBD structure were analyzed using Bioedit, followed by protein modelling using SwissModel and PyMol applications. The result showed that the SARS-CoV-2, MERS-CoV, and SARS-CoV genome shared the same genes yet in different numbers and length. SARS-CoV-2 Spike protein sequence was quite similar to SARS-CoV Spike protein, but very different to the Spike protein of MERS-CoV. There were variations of RBDs RBM structure due to the mutations occurred among these viruses. It is suggested that these differences may increase the affinity between SARS-CoV-2 Spike protein to its hACE2 receptor which caused SARS-CoV-2 becomes more infective and spread wider than SARS-CoV and MERS-CoV, in turn. This result expected to be basic information for the development of SARS-CoV-2 introduction inhibition agent and spreading prevention.